The Role of Digital Banking in Enhancing Financial Inclusion - Ikmanila, Regina; Djastuti, Indi (LifeSciFi, 2025)
Access to affordable and safe financial services is a key determinant of economic participation and growth. However, some part of the Indonesian population is still unbanked. The financial inclusion index in 2023 was only 75.02%. This gap in financial access creates challenges and opportunities to achieve broader economic goals. Digital banking is present as a transformative solution to expand financial access in more inclusive manner that benefits underserved groups, including rural communities, low-income populations, and MSMEs. This study uses the Systematic Literature Review (SLR) method to examine the role, strategies, innovations, and challenges of digital banking in driving financial inclusion. Case studies from Kenya, India, and Peru show how digital banking has a positive impact on financial inclusion through various innovations such as mobile banking and digital payment platforms. Some of the challenges hindering the realization of digital banking include limited digital infrastructure, low financial and digital literacy, regulatory barriers, cybersecurity risks, and lack of public trust. The research findings highlight the need for collaborative efforts between governments, financial institutions and technology providers to build an inclusive and secure digital financial ecosystem.